Kritik Atas Tashkik Jalaluddin Rakhmat Terhadap Validitas Hadis Puasa Asyura - Muhammad Kudhori, Kudhori (Mahad Aly Al Fithrah, 2023)
The fasting of Asyura has become sunnah tradition which is very popular among Moslem since long time ago. But, the existentialist of sunnah fasting Asyura get a critic from Jalaluddin Rakhmat in his book “Islam Aktual”. Based on Jalaluddin Rakhmat, the hadith that explain about the fasting that came from Ibn ‘Abbas is having a problem, because Ibn ‘Abbas who told the hadith did not see the occasion directly. Rakhmat also said that some hadiths in Asyura fasting has a contradiction among others. His conclusion defines that the sunnah of Asyura fasting is the politic engineering of Bani Umayyah so as Moslem rusted about the affair of al-Husayn’s assassination in Karbala, 61 Hijriah. This article is written as an effort to re-research toward the critics of Rakhmat. This article is a qualitative research using library references (library research). Content analysis and descriptive-analytical are used as data analysis methods with a historical approach. According to History analytic and Hadith’s antecedent are obtained that hadith from Ibn ‘Abbas about the sunnah of fasting Asyura classified into sahih hadith, Mursal Sahabi Hadith. So as, it can be a hujjah. Some hadiths about Asyura fasting which are told by Prophet’s followers also do not have any contradiction among them. In conclusion, Asyura fasting still became a sunnah tradition which is suggested by Prophet Muhammad Saw. and it is done by his followers also. Asyura fasting is not a politic engineering of Bani Umayyah that has an aim to rust Moslem about the memory in Karbala because it is done by Moslem long time ago before the accident in Karbala happened.